2020
DOI: 10.1016/j.pedneo.2020.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal free carnitine and short chain acylcarnitine blood concentrations in 12,000 full-term breastfed newborns in relation to their birth weight

Abstract: Background: Free carnitine (C0) and short chain acylcarnitine (SCA) blood concentrations play a significant role in fatty acid oxidation process during the first days of life. The aim of this study was to demonstrate C0 and SCA concentrations in Dried Blood Spots (DBS) of full term breastfed infants in relation to their birth weight (BW) perinatally. Methods: Breastfed full term infants (n Z 12,000, 6000 males, 6000 females) with BW 2000

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Similar to our findings, Liu et al (19) found increased levels of other acylcarnitines in SGA patients. In a recent study, C0 was found to be higher in babies with birth weight between 2,000 and 2,500 g; however, the authors did not mention the gestational ages and the SGA or LGA status of these babies (7). Sanches-Pintos et al (32) demonstrated higher carnitine levels in LGA newborns than in AGA, and the subgroup analysis of LGA newborns showed that there was no difference in babies with mothers having GDM.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar to our findings, Liu et al (19) found increased levels of other acylcarnitines in SGA patients. In a recent study, C0 was found to be higher in babies with birth weight between 2,000 and 2,500 g; however, the authors did not mention the gestational ages and the SGA or LGA status of these babies (7). Sanches-Pintos et al (32) demonstrated higher carnitine levels in LGA newborns than in AGA, and the subgroup analysis of LGA newborns showed that there was no difference in babies with mothers having GDM.…”
Section: Discussionmentioning
confidence: 94%
“…Studies focusing on the relationship between metabolomics and fetal growth have emerged quickly in the past years. It has been thought that early postnatal metabolic profiles of low birth weight (LBW) and macrosomic babies might differ from the normal (6,7). Metabolomics based on amino acid and carnitine/acylcarnitine profile studies with liquid chromatography-tandem mass spectrometry (LC-MS/MS) may have a role in our understanding of fetal and early postnatal energy metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we detect five additional metabolites negatively associated with sPTB (Mann-Whitney U p < 0.05; FDR < 0.1; Fig 2a). In Black women, these include glycerophosphoserine (p = 3x10 -5 ), which was previously reported to be altered in preeclampsia 43 ; spermine (p = 2.4x10 -4 ), which has immuno-modulatory roles in the gut 23 , and was increased in the blood of preterm infants 44 ; hydroxybutyl carnitine (p = 2.6x10 -4 ), a ketocarnitine involved in lipid metabolism and which has been shown to be depleted in the blood of low birth weight full-term neonates 45,46 ; and glutamate gamma-methyl ester (p = 4.9x10 -4 ), a derivative of glutamate and a precursor of the inhibitory neurotransmitter GABA. Tyramine, a biogenic amine with neuromodulator activity 47 , was significantly lower in samples from white women who delivered preterm (p = 2.8x10 -4 ; Fig.…”
Section: Metabolite Associations With Sptb Interact With Race and Sptb Timingmentioning
confidence: 93%
“…A recent study suggested that the levels of C4 and C5 were barely changed over the birth weight. The differences in outcomes between studies could be attributed to variations in the study population, as we focused on preterm neonates while other studies examined full-term babies [ 14 ].…”
Section: Discussionmentioning
confidence: 99%